(10, 11)
Since M is the midpoint of PQ, that means that the distance between P and M is the same as the distance between M and Q. So the answer will be
(M-P)+M
Let's substitute the known values and do the math:
(M-P)+M
= M - P + M
= (1,7) - (-8,3) + (1,7)
= (1 - -8 + 1, 7 - 3 + 7)
= (10, 11)
So the location of point Q is (10, 11).
Let's verify that answer. If we calculate the average of P and Q, we should
get M. So
((-8 + 10)/2, (3+11)/2)
= (2/2, 14/2)
= (1, 7)
And we get the correct value for M, so our answer is correct.